Integration of transcriptomics and metabolomics data revealed role of insulin resistant SNW1 gene in the pathophysiology of gestational diabetes - Ravi Bhushan; Rimjhim Trivedi; Ritu Raj; Anjali Rani; Sangeeta Rai; Anima Tripathi; Shiv Govind Rawat; Ajay Kumar; Dinesh Kumar; Pawan K. Dubey (Scientific Reports)
Abstract Gestational Diabetes Mellitus (GDM) is an emerging maternal health problem with increasing incidences. The lack of complete understanding of its pathophysiological mechanisms and novel regulatory biomarkers makes early diagnosis difficult. High-throughput RNA sequencing and computational bioinformatics analyses were conducted to identify novel hub genes, and their regulatory mechanisms were validated through qRT-PCR, western blot, and siRNA-mediated knockdown studies. Intermediate metabolites and circulatory levels of amino acids in the serum of GDM patients and healthy controls were measured. Transcriptomic studies identified SNW1 as the most sensitive and specific biomarker, significantly up-regulated in GDM (fold change = 1.09; p < 0.001). Metabolomic studies indicated significantly elevated gluconeogenesis in GDM, evidenced by decreased levels of alanine and increased levels of pyruvate and glucose compared to controls. siRNA-mediated knockdown of SNW1 in PANC1 cells resulted in significant down-regulation of alanine aminotransferase (ALT/GPT) and insulin receptor substrate (IRS1), while glucose transporters (GLUT2/GLUT4) and insulin (INS) were significantly up-regulated at both mRNA and protein levels. This study identified SNW1 as a novel insulin-resistant gene that induces hyperglycemia by elevating gluconeogenesis and decreasing glucose uptake. SNW1 may be considered a potential therapeutic target with clinical utility for the management of GDM.